2014
DOI: 10.1371/journal.pone.0111243
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Metabotropic Glutamate Receptors Regulates Ribosomes of Cochlear Nucleus Neurons

Abstract: The brain stem auditory system of the chick is an advantageous model for examining changes that occur as a result of deafness. Elimination of acoustic input through cochlear ablation results in the eventual death of approximately 30% of neurons in the chick cochlear nucleus, nucleus magnocellularis (NM). One early change following deafness is an alteration in NM ribosomes, evidenced both by a decrease in protein synthesis and reduction in antigenicity for Y10B, a monoclonal antibody that recognizes a ribosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…mGluR2 is also expressed in the cochlear nuclei while the expression of mGluR4 and mGluR7 remains unclear (Lu, 2014). In vivo and in vitro studies in the chick cochlear nucleus, nucleus magnocellularis, have demonstrated that pharmacological blockade of groups I and II mGluR activation provokes neuronal degeneration, suggesting a pivotal role for these receptors in regulating neuronal survival (Nicholas and Hyson, 2004; Diaz et al, 2009; Carzoli and Hyson, 2011, 2014). The activation of these receptors also regulates glutamate uptake at the cochlear nucleus-auditory nerve synapse, preventing the excitotoxic accumulation of extracellular glutamate (Carzoli and Hyson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mGluR2 is also expressed in the cochlear nuclei while the expression of mGluR4 and mGluR7 remains unclear (Lu, 2014). In vivo and in vitro studies in the chick cochlear nucleus, nucleus magnocellularis, have demonstrated that pharmacological blockade of groups I and II mGluR activation provokes neuronal degeneration, suggesting a pivotal role for these receptors in regulating neuronal survival (Nicholas and Hyson, 2004; Diaz et al, 2009; Carzoli and Hyson, 2011, 2014). The activation of these receptors also regulates glutamate uptake at the cochlear nucleus-auditory nerve synapse, preventing the excitotoxic accumulation of extracellular glutamate (Carzoli and Hyson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies in the chick cochlear nucleus, nucleus magnocellularis, have demonstrated that pharmacological blockade of groups I and II mGluR activation provokes neuronal degeneration, suggesting a pivotal role for these receptors in regulating neuronal survival (Nicholas and Hyson, 2004; Diaz et al, 2009; Carzoli and Hyson, 2011, 2014). The activation of these receptors also regulates glutamate uptake at the cochlear nucleus-auditory nerve synapse, preventing the excitotoxic accumulation of extracellular glutamate (Carzoli and Hyson, 2014). Whole cell recordings in brain slice preparations demonstrated that the activity of mGluRs suppresses GABAergic transmission (Lu, 2007), highlighting their role in achieving balanced excitation and inhibition in the nucleus magnocellularis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that deprivation of the auditory nerve input disrupts protein synthesis in NM neurons [123]. Further studies have shown that this activity-dependent regulation of protein synthesis relies on activity of mGluRs [124,125], but not involve iGluRs [126]. Specifically, group I and II mGluRs are required to maintain protein synthesis in NM neurons, because blocking either group I or II mGluRs eliminates activity-dependent regulation of ribosomes in vitro [127,128] as well as in vivo [129].…”
Section: Mglurs In Avian Auditory Brainstemmentioning
confidence: 99%